Using fisher‐contributed secondary fins to fill critical shark‐fisheries data gaps. Issue 3 (4th February 2021) - Quinlan, Jessica R.; O'Leary, Shannon J.; Fields, Andrew T.; Benavides, Martin; Stumpf, Emily; Carcamo, Ramon; Cruz, Joel; Lewis, Derrick; Wade, Beverly; Amato, George; Kolokotronis, Sergios‐Orestis; Clementi, Gina M.; et al.
Abstract: Developing‐world shark fisheries are typically not assessed or actively managed for sustainability; one fundamental obstacle is the lack of species and size‐composition catch data. We tested and implemented a new and potentially widely applicable approach for collecting these data: mandatory submission of low‐value secondary fins (anal fins) from landed sharks by fishers and use of the fins to reconstruct catch species and size. Visual and low‐cost genetic identification were used to determine species composition, and linear regression was applied to total length and anal fin base length for catch‐size reconstruction. We tested the feasibility of this approach in Belize, first in a local proof‐of‐concept study and then scaling it up to the national level for the 2017–2018 shark‐fishing season (1, 786 fins analyzed). Sixteen species occurred in this fishery. The most common were the Caribbean reef ( Carcharhinus perezi ), blacktip ( C. limbatus ), sharpnose (Atlantic [ Rhizoprionodon terraenovae ] and Caribbean [ R. porosus ] considered as a group), and bonnethead ( Sphyrna cf. tiburo ). Sharpnose and bonnethead sharks were landed primarily above size at maturity, whereas Caribbean reef and blacktip sharks were primarily landed below size at maturity. Our approach proved effective in obtaining critical data for managing the shark fishery, and we suggest the tools developed as part of this program could be exported to other nations in this region and applied almost immediately if there were means to communicate with fishers and incentivize them to provide anal fins. Outside the tropical Western Atlantic, we recommend further investigation of the feasibility of sampling of secondary fins, including considerations of time, effort, and cost of species identification from these fins, what secondary fin type to use, and the means with which to communicate with fishers and incentivize participation. This program could be a model for collecting urgently needed data for developing‐world shark fisheries globally. Article impact statement : Shark fins collected from fishers yield data critical to shark fisheries management in developing nations. Abstract : Uso de Aletas Secundarias Proporcionadas por Pescadores para Llenar Vacíos Importantes de Información sobre las Pesquerías de Tiburones Resumen: Con frecuencia no se evalúan las pesquerías de tiburones del mundo en desarrollo ni cuentan con un manejo activo de sustentabilidad. Uno de los principales obstáculos para esto es la falta de información sobre las especies y la composición de los tamaños en las capturas. Probamos e implementamos una estrategia nueva y potencialmente aplicable en todas partes para la recolección de estos datos: la entrega obligatoria de las aletas secundarias de bajo valor económico (aletas anales) obtenidas de los tiburones desembarcados por parte de los pescadores y el uso de estas aletas para reconstruir las especies y tamaños en la captura. Usamos identificaciones genéticas de bajo costo e identificaciones visuales para determinar la composición de las especies y aplicamos una regresión lineal a la longitud total y a la de la base de la aleta anal para la reconstrucción del tamaño en captura. Probamos la viabilidad de esta estrategia en Belice, primero en un estudio de prueba de concepto y después subiendo al nivel nacional para la temporada de pesca de tiburón 2017–2018 (1, 786 aletas analizadas). Se registraron 16 especies en esta pesquería. Las más comunes fueron Carcharhinus perezi, C. limbatus, Rhizoprionodon terraenovae y R. porosus (consideradas como un grupo) y Sphyrna cf . tiburo . Las últimas tres especies fueron desembarcadas principalmente por encima del tamaño maduro, mientras que con las dos primeras especies lo hacían por debajo del tamaño maduro. Nuestra estrategia demostró ser efectiva en la obtención de información crítica para el manejo de la pesquería de tiburones y sugerimos que las herramientas desarrolladas como parte de este programa puedan ser exportadas a otras naciones en esta región y aplicadas casi de manera inmediata si existen los medios para comunicarse con los pescadores e incentivarlos a proporcionar las aletas anales. Fuera del Atlántico Occidental tropical, recomendamos una mayor investigación de la viabilidad del muestreo de aletas secundarias, incluyendo la consideración del tiempo, esfuerzo y costo de la identificación de especies a partir de estas aletas; cuál tipo de aleta secundaria utilizar; y los medios mediante los cuales comunicarse con los pescadores e incentivarlos a participar. Este programa podría ser un modelo para la recolección de información de necesidad urgente para las pesquerías del mundo en desarrollo. 【摘要】: 发展中国家的鲨鱼渔业通常没有得到可持续性评估或积极管理; 其中一项基本障碍是缺乏关于物种和大小组成的渔获数据。我们测试并实施了一种可能广泛适用的新方法来收集这些数据, 即强制渔民上交捕获鲨鱼的低价值次级鱼鳍 (臀鳍), 并利用这些鳍确定捕获的物种及其大小。我们采用目测和低成本遗传鉴定的方法确定了渔获中的鲨鱼物种组成, 并基于体长和臀鳍基部长度的关系用线性回归对捕获鲨鱼的大小进行重建。我们在伯利兹测试了这种方法的可行性, 首先在局部地区进行概念验证研究, 然后在 2017–2018 年的鲨鱼捕捞季将其扩大到国家水平 (共分析 1786 个鱼鳍) 。该地区的渔场中有十六种鲨鱼, 最常见的是加勒比真鲨 ( Carcharhinus perezi ) 、黑边鳍真鲨 ( C. limbatus ) 、斜锯牙鲨 (大西洋斜锯牙鲨 [ Rhizoprionodon terraenovae ] 和加勒比斜锯牙鲨 [ R. porosus ] 被认为是一个群体), 以及窄头双髻鲨 ( Sphyrna cf . tiburo ) 。捕获的斜锯牙鲨和窄头双髻鲨的大小多数超过成年体型, 而加勒比真鲨和黑边鳍真鲨则大多低于成年体型。结果证明, 我们的方法可以有效地获得关键数据以管理鲨鱼渔业, 我们还建议将该项目开发的工具出口到该地域的其他国家, 且如果有与渔民沟通和激励他们提供臀鳍的渠道, 则可以立刻采取应用。在热带大西洋西部以外, 我们建议进一步研究对次级鱼鳍进行采样的可行性, 包括考虑时间、工作量、用鱼鳍进行物种鉴定的成本、使用什么鳍片类型以及采取什么方式与渔民沟通和激励参与。这个项目可以为全球发展中国家鲨鱼渔业收集迫切需要的数据提供范本。【翻译: 胡怡思; 审校: 聂永刚】